PENGARUH LINGKUNGAN KERJA DAN GAYA KEPEMIMPINAN MELALUI KEPUASAN KERJA SEBAGAI MEDIASI TERHADAP KINERJA KARYAWAN - ANNUR, MUHAMMAD RIZKI ALLAM; WIDAYATI, NURTI (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
The purpose of this research is to determine the influence of the work environment and leadership style through job satisfaction as a mediating variable on employee performance at PT.XYZ. The population used in this research was 80 people and the sample used in this research was the entire population, namely 80 people using a saturated sampling technique. Data collection was carried out by distributing questionnaires to all respondents, then the data was analyzed using SEM (Structural Equation Modeling) analysis using the measuring tool SmartPLS4 version 4.1.0.4. The results of this research show that the work environment and leadership style influence employee performance, but only the work environment influences job satisfaction. Job satisfaction has no effect on employee performance and does not have a role as a mediating variable between the work environment and leadership style on employee performance.